Edukasi Penggunaan Obat Tradisional Pada Terapi Penyakit Degeneratif di Kelurahan Magersari Magelang - Widarika Santi Hapsari; Puspite Septie Dinata; Herma Fanani Agusta; Ni Made Ayu Nila Septianingrum (Jurnal Abdi Masyarakat Kita, 2023)
Based on Riskesdas 2018, there are still many Indonesians who use traditional medicine. Organizations such as PKK (Family Welfare Development), can play a role and be more effective in socializing knowledge and utilization of medicinal plants. We use a method where participants take an active role in the activity so that the objectives of the activity will be easier to obtain. The activity was carried out in several stages, namely counseling and training on the use of medicinal plants. The training on the use of medicinal plants is in the form of training on the use of medicinal plants, namely a combination of Trigonella, Cinnamon, Green Tea and Salam Leaf which has the property of lowering blood glucose levels. From this activity, participants gain knowledge and skills about various types of medicinal plants and how to use medicinal plants and their processing